Epinephrine-Induced Mobilization of Natural Killer (NK) Cells and NK-like T Cells in HIV-Infected Patients - Søndergaard, Sisse R.; Ullum, Henrik; Skinhøj, Peter; Pedersen, Bente K. (Cellular immunology, 1999)
HIV infection is known to cause changes in phenotype and function of natural killer (NK) cells. The aim of this study was to characterize the NK cells mobilized from peripheral reservoirs in human immunodeficiency virus (HIV)-infected patients and controls. Seventeen HIV-infected patients and eight age- and sex-matched controls received a 1-h epinephrine infusion. Epinephrine induced mobilization of high numbers of NK-like T cells with no difference between HIV-infected patients and controls. Interestingly, all subjects mobilized NK cells containing increased proportions of perforin, in particular the CD3−CD16+CD56+ NK cell subset. The HIV-infected patients mobilized CD3−CD16−CD56+ and CD3−CD16+CD56+ NK cells to a lesser extent than did controls. In contrast, the HIV-infected patients mobilized relatively more CD3−CD16+CD56− NK cells independent of antiretroviral treatment. It is suggested that these cells represent an immature NK cell subpopulation possibly resulting from an impaired cytokine tissue environment in HIV-infected patients.